BIMBINGAN TEKNIS MEWUJUDKAN DESA MANDIRI MELALUI PROGRAM PRIORITAS: BEST PRACTICE DI DESA BORO-BORO KECAMATAN RANOMEETO PROVINSI SULAWESI TENGGARA - Ariani, Wa Ode Rachmasari; M. Natsir; Tajuddin; Tamburaka, Irmawatty P; Lapau, Fitri (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The Village Development Index (IDM) divides villages into five levels, namely very underdeveloped villages, underdeveloped villages, developing villages, advanced villages, and independent villages. This division aims to provide clarity in determining the level of progress of a village, as well as to establish a scale of priorities for formulating appropriate policy planning. Based on data released by the Ministry of Villages, Disadvantaged Regions, and Transmigration (Kemendesa PDTT), in 2024, Boro-Boro Village will be categorized as a developing village. Therefore, it is necessary to provide technical guidance on developing priority programs to help Boro-Boro Village become a self-sufficient village. This technical guidance aims to improve the ability of village officials to develop effective and efficient priority programs. The technical guidance method uses a participatory and collaborative approach, involving village officials and other stakeholders. The results of the technical guidance show that village officials now have a better ability to develop priority programs and increase village independence.   Keywords: IDM, Independent Village, Priority Program